جدليّة العلاقة بين الداخل والخارج في عالم عبد الرحمن منيف الروائي " رواية حين تركنا الجسر نموذجاً " - مروشيه محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
مبتغى هذا البحث يتوقف عند جدلية العلاقة بين الداخل والخارج في روائية عبد الرحمن منيف ليكشف جوهر الصراع بين الشرق والغرب، ويجلو أشكال توظيف هذه العلاقة وانعكاساتها على الواقع العربي ، وموقف الإنسان في الغرب- الشرق من هذه العلاقة. كما يهتم البحث بمناقشة القضايا الإشكالية المثارة حول آفاق الحلم العربي الذي كان ينوس بين فضائين: الأول هو التاريخ العربي بإخفاقاته ونكوصه، والفضاء الثاني هو نجاح العالم الآخر(الخارج) في بناء عالم جديد يقوم على النقد والتجريب والاكتشاف. This paper addresses the dialectics of the relationship between Abdul Rahman Muneef’s internal and external narrative world as presented in his When We Left the Bridge, so as to explore the essence of the conflict between the East and the West. It also tries to foreground the forms through which this relationship is employed and its implications for the condition of the Arab World as well as the attitude of the individual in both East and West toward that relationship. Furthermore, the paper discusses problematic issues related to the prospects of the Arab Dream, which alternates between two spaces: first, Arab history with its failures and setbacks; second, the success of the West in constructing a new world based on experimentation and exploration.